Let u = 1 + 3 ! x 3 + 6 ! x 6 + 9 ! x 9 + ⋯
and v = x + 4 ! x 4 + 7 ! x 7 + 1 0 ! x 1 0 + ⋯
and w = 2 ! x 2 + 5 ! x 5 + 8 ! x 8 + ⋯
Then what is u 3 + v 3 + w 3 − 3 u v w = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thank you for the solution. It is the first time l see this problem solved in this manner, nice solution. There is nothing serious behind the story of my name. Hana Wehbi is just my original name.
Log in to reply
Alright then. There is a "cheater" solution: Since the answer is numerical, we can simply check the case where x = 0 , which gives you the answer of 1 right away.
Hey there, Hana! This particular series problem actually appeared in the Purdue University "Problem Of The Week" publication (GO BOILERS!) I was one of the listed solvers back in Fall 2011.....thanks for the memories!
A detailed solution is worked out here:
Thanks for the solution. I saw your name among the solvers. I honestly got this problem from a Calculus book by Stewart 6 ed.
Log in to reply
Yup, back from my old Tampa, FL days!
Problem Loading...
Note Loading...
Set Loading...
Let α be a primitive cube root of unity. Then u + v + w u + α v + α 2 w u + α 2 v + α w = 1 + x + 2 ! x 2 + 3 ! x 3 + 4 ! x 4 + 5 ! x 5 + ⋯ = n = 0 ∑ ∞ n ! x n = e x , = 1 + α x + α 2 ⋅ 2 ! x 2 + 3 ! x 3 + α ⋅ 4 ! x 4 + α 2 ⋅ 5 ! x 5 + ⋯ = n = 0 ∑ ∞ n ! ( α x ) n = e α x , = 1 + α 2 x + α ⋅ 2 ! x 2 + 3 ! x 3 + α 2 ⋅ 4 ! x 4 + α ⋅ 5 ! x 5 + ⋯ = n = 0 ∑ ∞ n ! ( α 2 x ) n = e α 2 x .
Multiplying, we get ( u + v + w ) ( u + α v + α 2 w ) ( u + α 2 v + α w ) = e x + α x + α 2 x . This reduces to u 3 + v 3 + w 3 − 3 u v w = 1 .
I notice that "Nakkache" became "Wehbi". Is there a story behind that?